Psychological distress among infertile couples: exploring gender differences on psychological impacts of infertility and their relation to quality of life at Hospital Sultan Ismail Johor Bahru / Noorfaizah Ibrahim - Ibrahim, Noorfaizah (2019)
Infertility is an intense situation experienced by couples which cause an emotional discomfort and resulting in worsening their quality of life. Previous studies proved that couples with infertility are associated with psychological distress and hence impacts their quality of life not only in women but in male partners too. However, clinician usually failed to recognize this psychological distress and its impacts on the quality of life among these couples who were undergoing fertility treatment. Until now, there is a scarcity of journals and articles documenting on psychological distress among infertile couples in Malaysia. There is a need for a better care and understanding on what these couples had gone through in order to help them cope better and overall will increase the successful treatment rate. This research aim is to determine the gender differences in psychological distress and its associated risk factors among the infertile couples attending fertility clinic and how these factors are associated with Quality of Life (QoL). This study incorporated a cross-sectional study design involving one hundred couples attended the Fertility Clinics at Hospital Sultan Ismail Johor Bahru. Level of depression, anxiety and stress were measured using Depression, Anxiety and Stress Scale (DASS) while Quality of Life was measured by a specific and objective tool, Fertility Quality of Life (FertiQoL). The validated Malay versions of these questionnaires were used. This research results suggested that depression, anxiety and stress were reported at a higher level by wives than husbands with score ± SD (8.8 ± 4.57 vs. 5.9 ± 4.07, p<0.001, 8.6 ± 4.03 vs. 6.6 ± 4.36, p<0.001, and 13.0 ± 7.49 vs. 8.0 ± 6.36, p<0.001, respectively). Both the Core and Total FertiQoL score ± SD were significantly higher in the husbands of infertile couples than their wives (83.24 ± 12.12 vs. 73.85 ± 8.69, p<0.001, and 80.40 ± 10.29 vs. 73.79 ± 7.83, p<0.001, respectively). However, no significant differences were found in the Treatment domains between wives and husbands. Significant association were also found between the duration of infertility, duration of the marriage, gender and types of infertility with depression, stress and anxiety; while QoL significantly associated with gender, types and causes of infertility and history of receiving Intrauterine Insemination. In addition, a significant correlation was also found between depression, stress, anxiety and QoL. Based on these findings, it is crucial to have a continuous yet progressive awareness on the psychological aspect of infertility, focusing on each stage of treatments and medical interventions to decrease the psychological burden of the infertile couples and thus, to prevent the development of the psychological disorder.